Efektivitas Model Numbered Head Together (NHT) Berbantuan Media Video Animasi Terhadap Hasil Belajar Matematika SD - Purbo Ningrum, Dian; Sutriyani, Wulan (Pendidikan Matematika Universitas PGRI Yogyakarta, 2024)
The low achivement of students in mathematics is often caused by a lack of innovation and variety implemented by teachers in the use of teaching models and media. As a result, students become bored with learning mathematics, and their learning outcomes decline. Additionally, students’ understanding of mathematical concepts remains insufficient. This study aims to determine the effectiveness of using the Numbered Head Together (NHT) teaching model supported by animated video media on mathematics learning outcomes, specifically in the topic of whole number operations in garde IV at SD Negeri 6 Bulungan, and to test the difference in learning outcomes before and after using the NHT model. This research uses a quantitative approach with a Pre-Experimental design of the One Group Pretest-Posttest type. The sample consist of 15 students. The result show Tcount = 7,946 and Ttable = 2,144 at α = 0,05. Based on the criterion Tcount > Ttable, H0 is rejected and Ha is accepted. Additionally, descriptive analysis shows that the average pretest score of students was 59,00 which increased to 78,33 in the posttest. Therefore, the use of the Numbered Head Together (NHT) teaching model supported by animated video media is effective for elementary school students mathematics learning outcomes. Keywords: NHT, Learning Outcomes, Animated Video